Yarning as an Interview Method for Non-Indigenous Clinicians and Health Researchers - Byrne, A.L.; McLellan, S.; Willis, E.; Curnow, V.; Harvey, C.; Brown, Janie; Hegney, D. (SAGE PUBLICATIONS INC, 2021)
In this article, we discuss the origins, epistemology, and forms of Yarning as derived from the literature, and its use in research and clinical contexts. Drawing on three Yarns, the article addresses the extent to which non-Indigenous researchers and clinicians rightfully use and adapt this information-gathering method, or alternatively, may engage in yet another form of what can be described as post-colonialist behavior. Furthermore, we argue that while non-Indigenous researchers can use Yarning as an interview technique, this does not necessarily mean they engage in Indigenous methodologies. As we note, respectfully interviewing Aboriginal and Torres Strait Islander peoples can be a challenge for non-Indigenous researchers. The difficulties go beyond differences in language to reveal radically different expectations about how relationships shape information giving. Yarning as a method for addressing cross-cultural clinical and research differences goes some way to ameliorating these barriers, but also highlights the post-colonial tensions.